2015
DOI: 10.1259/dmfr.20140422
|View full text |Cite
|
Sign up to set email alerts
|

A newin vitromethod to evaluate radio-opacity of endodontic sealers

Abstract: Objectives: To evaluate a new method for assessing the radio-opacity of endodontic sealers and to compare radio-opacity values with a well-established standard method. Methods: The sealers evaluated in this study were AH Plus ® (Dentsply DeTrey GmbH, Konstanz, Germany), Endo CPM Sealer (EGEO SRL, Buenos Aires, Argentina) and MTA Fillapex ® (Angelus Dental Products Industry S/A, Londrina, Parana, Brazil). Two methods were used to evaluate radio-opacity: (D) standard discs and (S) a tissue simulator. For (D), te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Adobe Photoshop is already widely used in the dental and oral maxillofacial disciplines for measurement. 22,23 Intraoral radiographs were scanned at 1600 dpi, and panoramic radiographs were scanned at 300 dpi and saved as jpeg images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adobe Photoshop is already widely used in the dental and oral maxillofacial disciplines for measurement. 22,23 Intraoral radiographs were scanned at 1600 dpi, and panoramic radiographs were scanned at 300 dpi and saved as jpeg images.…”
Section: Methodsmentioning
confidence: 99%
“…Adobe Photoshop is already widely used in the dental and oral maxillofacial disciplines for measurement. 22,23 Intraoral radiographs were scanned at 1600 dpi, and panoramic radiographs were scanned at 300 dpi and saved as jpeg images.The radiographs were evaluated by two trained experienced oral and maxillofacial radiologists (DM, MD) tested for interobserver and intraobserver reliability; 24 the observers performed the assessment on all digital and scanned radiographs under the same conditions. 24 Differences between digital and scanned images were deemed clinically insignificant.…”
mentioning
confidence: 99%
“…The generated images (TIFF format) were encoded and analyzed by one blinded and calibrated examiner (ICC=1), as described by Malka et al (7). Briefly, the examiner evaluated the images at a 50 cm distance from a 24-inch liquid crystal display monitor under dimmed light.…”
Section: Radiopacity Assessmentmentioning
confidence: 99%
“…In a recent investigation, a new in vitro method was proposed to evaluate radiopacity of endodontic materials using a tissue simulator to approximate radiopacity evaluation to the clinical reality. It was observed that the superimposition of anatomical structures increases the filling material radiopacity (7). So, since most root canal fillings are distinguished from anatomical structures during radiographic analysis, even in smaller diameters than 1 mm, is important to investigate the gutta-percha radiopacity in thinner samples than the recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…282 Alternatively, a clinically relevant test based on the clinical appearance and usage of MTA in radiographs could be considered, 283 possibly in a tissue simulator model with teeth and bone. 284 Solubility affects radiopacity with more soluble MTAs illustrating greater loss of radiopacity over time. 223 Future studies should assess changes in radiopacity as dissolution occurs.…”
Section: Radiopacity (Iso 6876 and 9917-1)mentioning
confidence: 99%